1989
DOI: 10.1111/j.1471-4159.1989.tb07399.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Glucose Transporter at the Blood‐Brain Barrier and in Cerebral Cortex in Alzheimer Disease

Abstract: We studied the hexose transporter protein of the frontal and temporal neocortex, hippocampus, putamen, cerebellum, and cerebral microvessels (which constitute the blood-brain barrier) in Alzheimer disease and control subjects by reversible and covalent binding with [3H]cytochalasin B and by immunological reactivity. In Alzheimer disease subjects, we found a marked decrease in the hexose transporter in brain microvessels and in the cerebral neocortex and hippocampus, regions that are most affected in Alzheimer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
204
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(224 citation statements)
references
References 28 publications
20
204
0
Order By: Relevance
“…The reported decrease in glucose uptake mediated by stress or by high levels of GCs could place neurons in an energy-compromised environment, which could detrimentally affect neuronal responsiveness to pathophysiological events. In fact, glucose transport impairment precedes ATP depletion in brain, increasing neuronal vulnerability to excitotoxicity by compromising function of ion-motive ATPases (Mark et al, 1995), as it has been seen to occur in some neurodegenerative processes such Ab-induced toxicity, schizophrenia and others (Novelli et al, 1988;Kalaria and Harik, 1989;Sims, 1990;Mark et al, 1997;McDermott and De Silva, 2005) in which the reduction in glucose uptake occurs as an early step in the disease process prior to neuronal degeneration (Pettegrew et al, 1994;Reiman et al, 1996). On the other hand, GCs promote reduction in ATP levels (Tombaugh and Sapolsky, 1992;Lawrence and Sapolsky, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The reported decrease in glucose uptake mediated by stress or by high levels of GCs could place neurons in an energy-compromised environment, which could detrimentally affect neuronal responsiveness to pathophysiological events. In fact, glucose transport impairment precedes ATP depletion in brain, increasing neuronal vulnerability to excitotoxicity by compromising function of ion-motive ATPases (Mark et al, 1995), as it has been seen to occur in some neurodegenerative processes such Ab-induced toxicity, schizophrenia and others (Novelli et al, 1988;Kalaria and Harik, 1989;Sims, 1990;Mark et al, 1997;McDermott and De Silva, 2005) in which the reduction in glucose uptake occurs as an early step in the disease process prior to neuronal degeneration (Pettegrew et al, 1994;Reiman et al, 1996). On the other hand, GCs promote reduction in ATP levels (Tombaugh and Sapolsky, 1992;Lawrence and Sapolsky, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Marked declines in cerebral glucose metabolism are associated with Alzheimer's disease, especially in the parietal and temporal cortices (28,29,37,54). Initial studies by Kalaria and Harik (59) demonstrated a reduction in the 55-kDa form of GLUT1 in cerebral microvessels prepared from Alzheimer's patients compared with normal age-matched controls (60). These observations were confirmed and extended in studies by Simpson et al, who also demonstrated a loss of the 45-kDa glial form of GLUT1 and a striking loss of GLUT3 protein expression in parietal, occipital, and temporal cortex, together with caudate nucleus and hippocampus; only the frontal cortex did not show any significant loss (109).…”
Section: Neuronal Glut3 and Cerebral Glucose Utilizationmentioning
confidence: 99%
“…Loss of BBB structural integrity and function plays a pivotal role in the pathogenesis of many diseases of the central nervous system (CNS). The BBB is altered in many clinical settings including brain trauma (Unterberg et al, 2004), focal brain ischemia (Latour et al, 2004), meningitis (van der et al, 2004), brain tumor (Lee et al, 2006), stroke (Cipolla et al, 2004), inflammation (Stamatovic et al, 2006), Alzheimer's disease (Kalaria, 1992), and multiple sclerosis (Minagar and Alexander, 2003). In ischemic brain injury, matrix metalloproteinases (MMPs) contribute to the disruption of the BBB leading to vasogenic edema, and to the influx of leukocytes into the CNS (Gasche et al, 2006).…”
Section: Introductionmentioning
confidence: 99%